Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.4021/wjnu27w
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Fibrate-Induced Creatinine Elevation: Observations in an Outpatient Setting

Abstract: Background: A reversible rise in creatinine with fibrates has been previously documented. However, this phenomenon remains poorly understood with no associated factors described. We wished to study changes seen in creatinine following fibrate therapy in a routine outpatient setting and identify related risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Significant changes were seen in TC, TG and HDL-C following fibrate treatment. These findings were anticipated as our patient group was a subset of the cohort previously reported regards the above analytes (Ramachandran et al, 2012 ; Abbas et al, 2012 ). All three LFT studied decreased (Table 1 ) with fibrate treatment with paired t -Test showing the changes to be significant; GGT (p < 0.0001), ALT (p = 0.0014) and ALP (p < 0.0001).…”
Section: Resultsmentioning
confidence: 65%
“…Significant changes were seen in TC, TG and HDL-C following fibrate treatment. These findings were anticipated as our patient group was a subset of the cohort previously reported regards the above analytes (Ramachandran et al, 2012 ; Abbas et al, 2012 ). All three LFT studied decreased (Table 1 ) with fibrate treatment with paired t -Test showing the changes to be significant; GGT (p < 0.0001), ALT (p = 0.0014) and ALP (p < 0.0001).…”
Section: Resultsmentioning
confidence: 65%
“…In the study by Abbas et al [1] the use of a Jaffe creatinine assay presents a potential problem, since, unlike the enzymatic method used in our study, this method is prone to a range of analytical interferences. The findings, however, are still of interest.…”
Section: To the Editormentioning
confidence: 91%
“…
We read with interest a recently published study by Abbas et al in which the authors discussed the factors associated with the well-established rise in creatinine associated with fibrate treatment. They retrospectively analysed the case notes from a lipid clinic database of 132 patients [1].In accord with a number of studies published in the last 13 years (Tsimihodimos et al [2], Hottelart et al [3], Ansquer et al [4] ), interalia, the authors have shown a fibrate-associated increase in creatinine. In a recent prospective study, in hyperlipidaemic patients attending a lipid clinic [5] we have demonstrated a similar rise in serum creatinine using a Siemens enzymatic creatinine assay (Siemens Healthcare Diagnostics, Frimley, UK), which is traceable to isotope dilution/ mass spectrometry (ID/MS).
…”
mentioning
confidence: 89%
See 1 more Smart Citation